1976
DOI: 10.1111/j.1540-5915.1976.tb00723.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF TWO NORMATIVE STRUCTURAL INTERVENTIONS ON ESTABLISHED AND AD HOC GROUPS: IMPLICATIONS FOR IMPROVING DECISION MAKING EFFECTIVENESS1

Abstract: This paper focuses on a direct comparison of consensual, nominal, and conventional decision making techniques in established and ad hoc groups. The impact of the structural interventions on group decision quality and group attitudes is examined, and the appropriateness of the techniques in various situations is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1

Year Published

1984
1984
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 13 publications
4
35
1
Order By: Relevance
“…The consensus model (Harley, 1996) tested in this study is a structured model and, in this regard, differs from other consensus models reported in the literature (Hall & Watson, 1971;Nemiroff et al, 1976;Nemiroff & King, 1975;Schweiger et al, 1986). It resembles the scientific model advocated by Bennis (2002), since it is structured for both inquiry and critical judgment.…”
Section: Organizational Problem-solvingmentioning
confidence: 92%
See 2 more Smart Citations
“…The consensus model (Harley, 1996) tested in this study is a structured model and, in this regard, differs from other consensus models reported in the literature (Hall & Watson, 1971;Nemiroff et al, 1976;Nemiroff & King, 1975;Schweiger et al, 1986). It resembles the scientific model advocated by Bennis (2002), since it is structured for both inquiry and critical judgment.…”
Section: Organizational Problem-solvingmentioning
confidence: 92%
“…A review of the literature uncovered a limited number of potential techniques: consensus model (Hall & Watson, 1971;Nemiroff et al, 1976;Nemiroff & King, 1975;Schweiger et al, 1986;Schweiger & Sandberg, 1989), nominal group technique (Nemiroff et al, 1976), dialectical inquiry (Schweiger et al, 1986;Schweiger & Sandberg, 1989), and devil's advocacy (Schweiger et al, 1986;Schweiger & Sandberg, 1989). Of these techniques, a particular consensus model (Harley, 1996) appeared to satisfy the criteria mentioned by Senge (1990) and was chosen for this study.…”
Section: Interventionmentioning
confidence: 98%
See 1 more Smart Citation
“…These contexts range from the uncovering of productivity problems (Morris, 1979) to the identification of consumer perceptions of major pre-search problems (Claxton et al, 1980). Nemiroff et al, (1976) compared consensus, nominal and conventional interacting group on decision quality, member attitudes, and time taken to accomplish the lost at Sea exercise designed by the authors, but they noted no marked advantage to an NGT approach. Herbert and Yost (1979), strongly supported the superiority of NGT groups to uninstructed, interacting groups in accuracy, better use of group resources, and improvement over average individual decisions (high synergy) by implementing it on NASA Decision Making Problem (a task with considerable intentional depth).…”
Section: State-of-the-artmentioning
confidence: 99%
“…The NGT presents several advantages to the researcher. It offers a well tested procedure which in one study was shown to be more effective at producing ideas than either the Delphi technique or discussion groups (Nemiroff et al, 1976). Green (1975) conducted a study of NGT vs. normal interactive groups to determine problems faced by students in electronic data processing.…”
Section: State-of-the-artmentioning
confidence: 99%